KONSEP PENDIDIKAN ISLAM MASA RASULULLAH DAN SAHABA - Rahman, Abdul (AL-MISBAH (Jurnal Islamic Studies), 2013)
Education is something that is essential for human life. Because of the importance of education, Islamic education puts a high position. This can be seen in the Qur'an and Hadith that explains a lot about education. This paper describes the intricacies of the concept of education at the time of the Prophet and his best friend. Prophet as uswatun hasanah for Muslims, of course, has a lot of incised gold ink on education. Similarly, the friends that are the best ummah after the Prophet, had left the pillars of Islamic education that is worth for us to learn and apply in life. As the next generation of the Islamic caliphate, Muslims today should always explore the relics of the education system and the time of the Prophet Sahat. In this way, the Islamic education in the present and future will remain victorious.